Existence of the Environmental Kuznets Curve and its relevance to SDGs policy: A study in Java region, Indonesia - Ibrahim, Mochammad Daffa; Abbas, Muhammad Hasyim Ibnu (Publisher of Widyagama University of Malang (UWG Press), 2022)
The debate on economic growth as a trigger or solution to environmental damage is the driving force behind this research. This study examines whether there is an advanced stage of the Environmental Kuznets Curve (EKC) that forms a curve resembling the letter N in Java province, Indonesia. This study used a panel data regression model with the main variableof CO2 emissions and GDP per capita. This research demonstrated that, in the short term, per capita income growth caused damage to the environment. However, this relationship was different in the long run and eventually formed an N-shaped curve. The existence of an N-shaped EKC was detected, but not significant. The relationship between population growth rates, income inequality and the Sustainable Development Goals (SDGs) with CO2 emissions as well as EKC turning points were also investigated in this study. The study results included N-shaped EKC detected in Java with the first turning point of Rp 154,297,936 and the second turning point of Rp 1,136,629,791. Population growth rate was proven not to affect CO2 emissions, in contrast to income inequality and the SDGs agreement which affected emissions in Java. Raising public awareness, paying attention to energy use, initiating technological innovations, and enforcing pro-environment policies are recommended to be implemented in Java and across Indonesia.JEL Classification: Q01; Q11; R11